Pengaruh E-Commerce Shope Terhadap Tingkat Penjualan Baju di Pasar 16 Ilir Palembang - Suci Daniya; Abdur Razzaq; M. Shaka Hidayatullah; Siti Mardia; Muhamad Yudistira Nugraha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to evaluate the extent to which the Shopee e-commerce platform affects the sales rate of clothes in Pasar 16 Ilir, Palembang, which is known as one of the largest clothing trading centers in South Sumatra. The background of this research departs from the phenomenon of the rapid development of e-commerce in Indonesia, where Shopee dominates the fashion category and is the main choice of consumers in online shopping. The change in consumer behavior from conventional to digital shopping patterns encourages businesses in traditional markets to adjust strategies to remain relevant and competitive in the increasingly dynamic era of digital transformation. This research method uses a combination of quantitative and qualitative approaches. A survey was conducted on 100 sellers and 150 consumers to collect data on shopping habits, perception of promotions, and the impact of using Shopee on clothing sales. In addition, in-depth interviews with several business actors at Pasar 16 Ilir were conducted to gain a more detailed understanding of the adaptation strategies they implemented. Data analysis shows that Shopee's promotional features, such as discounts, cashback, and flash sales, are the dominant factors that increase consumer interest. Hedonistic aspects, including the convenience and pleasure of online shopping, as well as customer reviews, also have a significant influence on purchasing decisions. The results of the study confirm that the integration of Shopee with the traditional market contributes to the increase in the volume and sales value of clothes in Pasar 16 Ilir. The online-to-offline (O2O) synergy model helps merchants reach a wider market and improve their competitiveness. In conclusion, optimizing e-commerce platforms through effective promotion strategies, review management, and customer service is the key for MSME actors in facing competition in the digital era.